Effects of biopolymer discharge from MBR mixture on sludge characteristics and membrane fouling - Wang, Zhiwei; Mei, Xiaojie; Wu, Zhichao; Ye, Shaofan; Yang, Dianhai (Chemical engineering journal (Lausanne, Switzerland : 1996), 2012)
[Display omitted] ► TMP was lowered after biopolymers were discharged in a uniquely designed MBR. ► SMP and their components were decreased after discharging biopolymers. ► HPI-N in SMP, showing large MW and strong fouling potential, was reduced. ► Zeta potential, sludge flocs size, and dewaterability were also changed. A new pathway was explored in order to gain insights into the role of biopolymers in sludge characteristics and membrane fouling. The biopolymers were discharged from a membrane bioreactor (MBR) using a unique design (called as dual-MBR in this study). The variations of soluble microbial products (SMP), extracellular polymeric substances (EPS), sludge surface charge, particle size and dewaterability were analyzed in the dual-MBR after the discharging of biopolymers from the system. It was found that carbohydrates in SMP, proteins in SMP and humics in SMP were decreased in the dual-MBR compared to the control-MBR. Gel filtration chromatography (GFC) analysis showed that the substances with macromolecular weight in SMP were reduced in the dual-MBR. Three-dimensional excitation–emission matrix (EEM) fluorescence spectra demonstrated that the aromatic protein-like substances in SMP were also lowered in the dual-MBR. The neutral hydrophilic (HPI-N) fraction in SMP, which was found to have larger molecular weight distribution and stronger fouling potential compared to the rest fractions, was significantly reduced in the dual-MBR. The exclusion of biopolymers from the dual-MBR also resulted in the decrease of the bound EPS and the reduction of proteins in bound EPS, which consequently caused the decrease of sludge surface charge, the increase of sludge flocs and the improvement of sludge dewaterability. The above changes induced by the exclusion of biopolymers can explain why the trans-membrane pressure in the dual-MBR exhibited a slower increase rate compared to the control-MBR. This study offered an evaluation of the contribution of biopolymers to sludge characteristics and membrane fouling through a different angle from previous publications.